O desenvolvimento profissional docente e a participação colegiado no Atheneu Norte-Riograndense - Oliveira, Vivianne Souza de (2006)
To investigate the relationship that exists among the educational participation of the school board and the teacher's professional development, starting from the analysis teachers of a public institution who teaches daily in the city of Natal. We focused the possible relationships between the teacher's action and their professional development, which includes the participation of the School board, considered by us as a collective space. To accomplish this research we used Interviews (KAUFMANN, 1996; SILVA, 2002) to analyze the nine participants, who are teachers' of the school board, and their oral speeches, considered as main references of our study. While trying to understand the reasons that led the teachers to choose her/his educational profession, we noticed the difficulty of recognition of the job of lecturing as a profession. This fact comes as an obstacle to the perspective of the teachers' professional development. In what he/she refers to the forms of the teachers' participation in the board and their meanings, we noticed in first place that the feeling of it belongs one of the decisive factors it can be considered actively for the teacher to announce of the actions colegiadas. This for them to want and they believe that that is the best road for if they develop better while professionals and consequently to improve the situation of the school. In second place we noticed that the school board represents, a place of articulation of the equality among all the ones that form the school community. So, we tried to understand how they happened to the collective actions in the school, how the teachers presented them in spite of what they know, how a collective action should be presented in the elements of fragility of that process that inhibit the development of the overall action. Finally, we questioned the elements that would contribute to the educational professional development; we noticed that the teachers present the competence, the ethics and professional valorization, as factors that contributed at the present time to their educational professional development